A 2-decade survival from a double hemolytic disease: A case of paroxysmal nocturnal hemoglobinuria with hemoglobinopathy - Aria Namiq Chaqmachi; Brwa Ali Hussein (Iraqi Journal of Hematology)
Due to a mutation in the phosphatidylinositol glycan class A (PIGA) gene, hemolytic anemia, thrombosis, and bone marrow failure are the hallmarks of the uncommon hematologic illness known as paroxysmal nocturnal hemoglobinuria (PNH). Although by different processes, hemoglobinopathies, such as thalassemia, can manifest with hemolytic anemia. The 40-year-old female patient in this case study had a complicated clinical presentation with both hemoglobinopathy – more precisely, a form of thalassemia – and PNH. Abdominal pain, fatigability, and dark urine episodes were the patient’s initial complaints. PNH was confirmed by laboratory testing, which showed low hemoglobin, increased lactate dehydrogenase, and hemosiderinuria. Thalassemia was discovered by a further hematologic workup. It is quite uncommon for hemoglobinopathy and PNH to coexist. This case emphasizes how crucial it is to perform a thorough hematologic examination on patients who have hemolytic anemia to customize treatment plans and enhance patient outcomes. We will discuss therapeutic hurdles, possible treatment choices, and the clinical journey of the patient with a classical type of PNH with access only to steroids, blood transfusions, and supplements.